Patients with symptoms of delayed gastric emptying have a high prevalence of oesophageal dysmotility, irrespective of scintigraphic evidence of gastroparesis - George Triadafilopoulos; John O Clarke; Linda Nguyen (BMJ Open Gastroenterology)
Background Patients with symptoms suggestive of gastroparesis exhibit several symptoms, such as epigastric pain, postprandial fullness, bloating and regurgitation. It is uncertain if such symptoms reflect underlying oesophageal motor disorder.Aims To examine whether patients with epigastric pain and postprandial distress syndrome suggestive of functional dyspepsia and/or gastroparesis also have concomitant oesophageal motility abnormalities and, if so, whether there are any associations between these disturbances.Methods In this retrospective cohort study, consecutive patients with functional gastrointestinal symptoms suggestive of gastric neuromuscular dysfunction (gastroparesis or functional dyspepsia) underwent clinical assessment, gastric scintigraphy, oesophageal high-resolution manometry and ambulatory pH monitoring using standard protocols.Results We studied 61 patients with various functional upper gastrointestinal symptoms who underwent gastric scintigraphy, oesophageal high-resolution manometry and ambulatory pH monitoring. Forty-four patients exhibited gastroparesis by gastric scintigraphy. Oesophageal motility disorders were found in 68% and 42% of patients with or without scintigraphic evidence of gastroparesis respectively, suggesting of overlapping gastric and oesophageal neuromuscular disorder. Forty-three per cent of patients with gastroparesis had abnormal oesophageal acid exposure with mean % pH <4.0 of 7.5 in contrast to 38% of those symptomatic controls with normal gastric emptying, with mean %pH <4.0 of 5.4 (NS). Symptoms of epigastric pain, heartburn/regurgitation, bloating, nausea, vomiting, dysphagia, belching and weight loss could not distinguish patients with or without gastroparesis, although weight loss was significantly more prevalent and severe (p<0.002) in patients with gastroparesis. There was no relationship between oesophageal symptoms and motor or pH abnormalities in either groups.Conclusions Irrespective of gastric emptying delay by scintigraphy, patients with symptoms suggestive of gastric neuromuscular dysfunction have a high prevalence of oesophageal motor disorder and pathological oesophageal acid exposure that may contribute to their symptoms and may require therapy. High-resolution oesophageal manometry and pH monitoring are non-invasive and potentially useful in the assessment and management of these patients.